Assessment of accuracy of oestrus detection by progesterone assay in cattle and buffaloes - KUMARESAN, A; ANSARI, M R; SANWAL, P C (The Indian Journal of Animal Sciences, 2014)
The accuracy of visual observations and clinical methods in detecting oestrus in cattle and buffaloes was assessed by analysing the level of plasma progesterone at the time of insemination. Both the methods were not error free in detectingoestrus. The percentage of cattle and buffaloes that were wrongly detected as in oestrus by visual observations were 11.05 and 20.75, and by clinical methods were 3.01 and 12.35 respectively. The conception rates in this group of animals were poor and the inseminations at low progesterone levels resulted in higher conception rates.